THE HUMAN PATHOGENS CARRIED BY THE COCKROACHES IN THE FOOD-RELATED ENVIRONMENT POTENTIALLY CAUSING A FOODBORNE DISEASES: A SYSTEMATIC REVIEW - Rizki Zahrotul Hayati; Dewi Susanna (Malaysian Journal of Public Health Medicine, 2020)
Cockroaches are one of the potential vectors on spreading disease and health problems for humans by contaminating foods, ingredients, or food storage. Cause of their habit and life in an unsanitary place, they can carry human pathogens in their body and contaminated. This review aims to know the types and prevalence of human pathogens carried by cockroaches in the food-related environment and discuss the possibility of human pathogens carried by cockroaches that can cause foodborne diseases. This systematic review conforms to the PRISMA guidelines. The initial search was done from four health-related electronic databases (PubMed Central, EBSCOhost, Proquest, and Scopus) for relevant literature on pathogens that isolated from the cockroaches. There are 129 articles identified in the initial search database. After screening and eligibility process, eight articles were identified for this review. It was found that most of the cockroaches captured in/around food handling establishment and human habitation. Furthermore, around 23 species pathogens, predominantly bacteria, were identified from the cockroaches. This review showed that cockroaches carry many pathogens, which can cause severe infections in humans, such as foodborne diseases through contaminated food.